Differential Outcome between BALB/c and C57BL/6 Mice after Escherichia coli O157:H7 Infection Is Associated with a Dissimilar Tolerance Mechanism - Bernal, Alan Mauro (2021)
Enterohemorrhagic Escherichia coli (EHEC) infections can result in a wide range of clinical presentations even though EHEC strain belongs to O157:H7 serotype, one of the most pathogenic ones. Although pathogen virulence influences disease outcome, we emphasize about the concept of host-pathogen interactions, which involve resistance or tolerance mechanisms in the host that finally determine host fitness and bacterial virulence. Taking advantage of the genetic differences between mouse strains, we analyzed the clinical progression in C57BL/6 and BALB/c weaned mice infected with an E. coli O157:H7 strain. We carefully analyzed colonization with several bacterial doses, clinical parameters, intestinal histology and the integrity of the intestinal barrier, as well as local and systemic levels of antibodies to pathogenic factors. We demonstrated that although both strains had comparable susceptibility to Shiga toxin (Stx) and the intestinal bacterial burden was similar, C57BL/6 showed increased intestinal damage and alteration of the integrity of the intestinal barrier, and impaired renal function that resulted in increased mortality. The increased survival rate in BALB/c strain was associated to an early specific antibody response as part of a tolerance mechanism.